R&D Spending and Stock Returns: Evidence from Germany - Standert, Roland (Journal of Accounting, Business and Finance Research, 2020)
The key purpose of this study was to investigate the significance and impact of R&D spending on stock returns. This study aimed to provide evidence from the public listed companies of Germany. The research design followed in this study was quantitative. Data has been collected from secondary sources, and from the time period of 2013 to 2019. In this manner, author has collected the data about total assets, debt to equity, stock price average and R&D spending of 22 public listed companies in Germany. Initially, the data analysis technique that has been used in this study was panel data technique; however, due to the occurrence of heteroskedasticity and autocorrelation in a data set, author has used GLS model for analysing the impact of R&D spending on stock return. The findings of this study reveal the significant impact of R&D spending on stock return. With respect to control variables, findings of this study also confirm the significant impact of firm size on R&D spending, where debt to equity was found to have a significant but negative impact on R&D spending.